2021
DOI: 10.1016/j.csbj.2021.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Implementing fluorescence enhancement, quenching, and FRET for investigating flap endonuclease 1 enzymatic reaction at the single-molecule level

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 112 publications
(233 reference statements)
0
9
0
Order By: Relevance
“…This was first demonstrated for sCy dyes by Steffen et al in the presence of different RNA structures (Figures 4(A), 5) [75]. The dependence of NAIFE on the chemical microenvironment can now be used to investigate the degree of folding of the nucleic acid or the interaction probability with binding partners, such as hybridising DNA fragments [86] or a recently developed DNA-aptamer sensor [87].…”
Section: Nucleic Acid-induced Fluorescence Enhancement (Naife)mentioning
confidence: 91%
“…This was first demonstrated for sCy dyes by Steffen et al in the presence of different RNA structures (Figures 4(A), 5) [75]. The dependence of NAIFE on the chemical microenvironment can now be used to investigate the degree of folding of the nucleic acid or the interaction probability with binding partners, such as hybridising DNA fragments [86] or a recently developed DNA-aptamer sensor [87].…”
Section: Nucleic Acid-induced Fluorescence Enhancement (Naife)mentioning
confidence: 91%
“…Additionally, several model systems of proteins and enzymes, such as endonucleases, polymerases, and lipases, involved in biological processes like DNA replication have been characterized with similar methods (i.e., single-molecule localization, confocal microscopy, and TIRF) to provide insight into kinetic mechanisms. 19,142,[213][214][215] As an example, Sobhy et al utilized FRET and confocal microscopy and found that flap endonuclease 1 (FEN1) blends DNA molecules in accordance with a diffusion-limited model. While DNA sequencing is not within the scope of this perspective, there are multiple studies and reviews discussing the applications of single-molecule techniques to image these processes.…”
Section: Biopolymer Systemsmentioning
confidence: 99%
“…We then focused on substrate conformational requirements and handoff mechanisms among MOF proteins. We previously deciphered conformational states during the FEN1 catalytic cycle using single-molecule FRET 13,14,36,37 (Fig. 2A).…”
Section: Reconstitution Of the Human Mof Reactionmentioning
confidence: 99%